Influence of Digital Transformation on Firm Performance in the Service Industry in United States - Smith, John (International Journal of Business Strategies, 2024)
Purpose: The aim of the study was to assess the influence of digital transformation on firm performance in the service industry in the United States. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The adoption of digital technologies such as cloud computing, big data analytics, and artificial intelligence has led to improved operational efficiency, enhanced customer experiences, and increased competitive advantage for service firms. These advancements have enabled firms to streamline processes, personalize services, and optimize resource allocation, thereby driving revenue growth and profitability. Moreover, digital transformation has facilitated greater agility and innovation, allowing firms to adapt to changing market dynamics and capitalize on emerging opportunities. However, challenges such as cybersecurity threats, data privacy concerns, and workforce skill gaps remain pertinent, highlighting the importance of strategic planning and investment in digital capabilities. Overall, the findings underscore the transformative power of digital technologies in shaping the performance and competitiveness of service firms in the United States. Implications to Theory, Practice and Policy: Resource-based view theory, institutional theory and dynamic capabilities theory may be use to anchor future studies on assessing the influence of digital transformation on firm performance in the service industry in the United States. Service firms should prioritize fostering a culture of innovation to support digital transformation initiatives effectively. Policymakers should work on creating supportive regulatory frameworks that encourage innovation and investment in digital technologies within the service industry.